In plain sight : impunity and human rights in Thailand - Haberkorn, Tyrell (New perspectives in Southeast Asian studies., 2018)
Following a 1932 coup d'etat in Thailand that ended absolute monarchy and established a constitution, the Thai state that emerged has suppressed political dissent through detention, torture, forced reeducation, disappearances, assassinations, and massacres. In Plain Sight shows how these abuses, both hidden and occurring in public view, have become institutionalized.